Copper, invisible impact - Brancoli, Bernardita (Base Diseño e Innovación, 2015)
Gabriela Mistral, poetize and Chilean Nobel prize, in her interpretation of Charle’s Perrault tale of Cinderella, incorporates copper within the precious metals. In her texts she speaks of “red brocades”, “copper and silver mysteries” and in the dance mentions a copper orchestra.